Workshop Report on Integrating Livestock Health and Management into Kenya’s Climate Policies - Ng'ang'a, Kevin Gitau; Cramer, Laura K. (International Livestock Research Institute, 2025)
Livestock are central to Kenya’s economy and rural livelihoods, but climate change is reshaping the sector. Rising temperatures, erratic rains, and extreme weather have already cut forage and water supplies. Meanwhile, livestock contribute significantly to global emissions: cattle and other ruminants emit methane through digestion, and manure and feed production generate greenhouse gases. Improving animal health is a practical response: healthier animals are more productive and may consume less resources per unit output. Workshop speakers highlighted that treating common diseases (parasites, mastitis, reproductive disorders, etc.) can improve growth and fertility while slightly raising total emissions, resulting in lower emissions per kilo of meat or milk produced. The workshop aimed to bridge the livestock and climate sectors: to map existing policies, identify who influences them, and understand how information (and gaps) flows between actors. By doing so, the project seeks to ensure Kenya’s climate strategies better recognise the co-benefits of animal health interventions.